A Sustainable Innovation: Functionalization of Pasta with Methanol Extract of Turkish Red Pine (Pinus brutia Ten.) Barks - Erol, Kubra Feyza; Kutlu, Gozde; Olgun, Elmas Oktem; Tornuk, Fatih (SPRINGER, 2025)
Turkish red pine (Pinus brutia Ten.) is an economically and ecologically important tree species that is widely grown in the Mediterranean and Aegean regions of T & uuml;rkiye, with its bark (RB) serving as waste material in the forest industry. The current study aims to quantify the phenolic composition of RB extract (RBE) and to investigate the effects of incorporating RBE into pasta at ratios of 0, 0.25, 0.50, and 1.00% (w: w) on in vitro starch digestibility, mineral composition, bioactive properties (including TPC, DPPH, and FRAP antioxidant activities), in vitro bioaccessibility of bioactive compounds, and sensory attributes. Gallic acid (2.30 mg/ 100 g) and hydroxybenzoic acid (3.80 mg/ 100 g) were the two predominant phenolic acids in RBE. Enrichment of the pasta with RBE (0.25%, 0.50%, and 1% w/w) resulted in higher mineral content, antioxidative properties, lower glycemic index and higher sensory scores as compared to the control pasta. Enrichment of pasta with 1% RBE resulted in a significant reduction in the hydrolysis index (HI) and predicted glycemic index (pGI), with HI values decreasing from 28.67 to 45.65% and pGI reductions ranging from 27.18 to 40.04%, indicating a notable negative impact on starch degradation and glucose release. Enrichment of pasta with RBE significantly increased the total phenolic content from 4.12 to 31.29 mg GAE/100 g and enhanced antioxidant activities, with FRAP values rising from 7.45 to 99.46 mu mol TEAC/100 g and DPPH activities ranging from 11.45 to 70.36 mu mol TEAC/100 g. Bioaccessibility index values for TPC, FRAP, and DPPH activities in pasta samples enriched with 1% RBE were determined to be 25.51%, 27.33%, and 43.03%, respectively, indicating a significant enhancement in the in vitro bioaccessibility and antioxidant potential of bioactive compounds as compared to the control sample. Enrichment with 1% RBE significantly increased calcium, potassium, magnesium, sodium, zinc, copper, iron, and manganese content of pasta, and contributed substantial percentages of the recommended dietary allowances for these minerals. Overall, the findings showed that RBE could be used as a functional ingredient in pasta formulation for increasing its nutritional and health beneficial properties.
Keywords: Pinus brutia; Bark; Pasta; In vitro starch digestibility; In vitro bioaccessibility; ANTIOXIDANT ACTIVITY; IN-VITRO; ACID; RESISTANCE; IMPACT; Environmental Sciences & Ecology